Trends and Issues in Global Tourism 2011 - Conrady, Roland; Buck, Martin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book provides insights into important trends and future scenarios in the global tourism and travel industry. It analyses today s challenges in the aviation and hospitality industry, in destination management, and in marketing and distribution management. New empirical data on general travel behaviour and the latest consumer trends are also presented. The contributors to this book are well-known individuals from important tourism, travel and consulting firms (e.g. BCD Travel, Öger Tours, Booz and Company, GfK, IPK International) and researchers from universities in Switzerland, United Kingdom, the Netherlands, and Germany. In addition institutes specializing in future research highlight important travel trends. Corporate social responsibility is one of the top themes to-be and therefore a focus of this book, offering insights into the concept of CSR, empirical data on consumer requests, corporate strategy issues and financial investment implications.
New Data on Tourism and Changing Travel Behaviour -- Challenges in Global Aviation Management -- Hospitality Management in a Changing Environment -- Destination Management: Product - Branding - Promotion -- Marketing Management in Global Tourism: Identifying New Opportunities -- Business Travel Management: Costs - Yield - Success -- Corporate Social Responsibility: Help or Hindrance? -- Beyond the Boundaries of the Tourism Industry.
Keywords: Economics; Geography; Regional economics; Industrial management; Human Geography; Economics/Management Science; Management/Business for Professionals; Regional/Spatial Science; Economic Geography; Human Geography